Persepsi followers @perpuseru terhadap akun instagram PerpuSeru menggunakan teori decoding-encoding - Lasenta Adriyana; Kuncoro Darumoyo (Universitas Padjadjaran, 2018)
Libraries have used media development as part of the culture to influence people to use the library. An example of the use of media as a means of mediation is the PerpuSeru program. Previously, this program partnered with 34 libraries, but currently, the PerpuSeru program has partnered with more than 400 libraries and reading parks in Indonesia. One of the media used in transferring information is Instagram; PerpuSeru has an Instagram account namely @perpuseru in which various information about the PerpuSeru program is available and the extent to which the program is running. The purpose of this study was to determine the extent of the followers’ perceptions in receiving information provided on the @ perpuseru Instagram by decoding-encoding theory, to examine the extent this theory developed in a media in the present era, and the role the theory played in the media. This study used the descriptive qualitative research method by interviewing some followers of the @perpuseru account. The result found two different views from followers, namely followers with a hegemonic dominant point of view who accepted all the content of information conveyed, and others with a negative perspective who had other considerations in receiving information on the posts of @perpuseru account. However, there were no followers with optional viewpoints. It can be concluded that the two perspectives of @perpuseru Instagram followers are the hegemonic and negative perspective.